THE TODA–YAMAMOTO CAUSALITY ANALYSIS OF THE RELATIONSHIP BETWEEN NATURAL GAS PRODUCTION AND ELECTRICITY CONSUMPTION IN IRAQ (2000–2023) - Hifaa Yousif Soleiman (Journal of Economic and Economic Policy, 2026)
Objective: This study sought to uncover the nature of the bidirectional causal relationship between natural gas production and electricity consumption in Iraq during 2000–2023 by employing the Toda–Yamamoto causality test, a key method for revealing relationships between economic time series with varying degrees of integration. Method: This study sought to uncover the nature of the bidirectional causal relationship between natural gas production and electricity consumption in Iraq during 2000–2023 by employing the Toda–Yamamoto causality test, a key method for revealing relationships between economic time series with varying degrees of integration. Results: The results of the Toda–Yamamoto causality test revealed a bidirectional relationship: an increase in natural gas production contributes to an increase in electricity consumption in Iraq, and an increase in electricity production and consumption contributes to an increase in natural gas production. These results confirm the importance of interdependence between the two sectors and that neither can grow without the other. Novelty: One of the most important recommendations from the research is the need for optimal utilisation of associated gas, which is automatically extracted with crude oil. The proportion of gas flared without being utilised amounts to approximately 20% of the gas produced in Iraq by 2025. This is a significant figure; associated gas must be optimally utilised for electricity production, thereby reducing reliance on gas imported from neighbouring countries.